PHB(Polyhydroxybutyrate) Production by Pseudomonas aeruginosa and its Application in Dye Decolorization - Patil M. S.; Kate V. V; Pawar P.P; Parate S. C; Ghuge G. K (Revista Electronica de Veterinaria, 2023)
Polyhydroxyalkanoates(PHAs) are class of biodegradable,biocompactible plastics composed of polyester of R-hydroxyalkanoic acids. Polyhydroxybutyrate(PHB) is a short chain of PHA that is naturally produced by several microorganisms as a reserve material. Its accumulated in bacteria as intracellular storage granules in the presence of excess carbon source and limited nitrogen source.The present work focused on the extraction of PHB from a gram negative bacteria P.aeruginosa and  its application in dye decolorization.  It showed  significant results in the degradation of crystal violet dye.   After the 64 hours of incubation,  a combination of PHB and Pseudomonas aeruginosa culture gives 92% color removal efficiency that is highest as compare to  individual treatment of PHB and Pseudomonas aeruginosa alone with dye.While individually treated dye with PHB and Pseudomonas aeruginosa alone gives 68% and 79.50% respectively. Thus, the combination of PHB and Pseudomonas aeruginosa culture is found to be significantly effective in decolorization of dye.